Developmental and physical-fitness associations with gross motor coordination problems in peruvian children - Chaves, Raquel Nichele de (2016)
he aims of this cross-sectional study were to examine the developmental characteristics (biological maturation and body size) associated with gross motor coordination problems in 5193 Peruvian children (2787 girls) aged 6–14 years from different geographical locations, and to investigate how the probability that children suffer with gross motor coordination problems varies with physical ﬁtness. Children with gross motor coordination problems were more likely to have lower ﬂexibility and explosive strength levels, having adjusted for age, sex, maturation and study site. Older children were more likely to suffer from gross motor coordination problems, as were those with greater body mass index. However, more mature children were less likely to have gross motor coordination problems, although children who live at sea level or at high altitude were more likely to suffer from gross motor coordination problems than children living in the jungle. Our results provide evidence that children and adolescents with lower physical ﬁtness are more likely to have gross motor coordination difﬁculties. The identiﬁcation of youths with gross motor coordination problems and providing them with effective intervention programs is an important priority in order to overcome such developmental problems, and help to improve their general health status.